Implementation of Technological Changes Among Automotive Vendors in SMIs - Wong, Yit Jih (2003)
The issue on technology changes in local SMIs have not been thoroughly investigated, and yet not well understood. This research is to study the implementation of technology change in one of Malaysian Automotive Industry, Proton, focusing mainly on the performance of its group of vendors. It is meant to provide an overview on how capable this group of vendors are in adapting to changes and consequently enable them to evaluate themselves among themselves. The research was carried out through survey based on a set of carefully designed questionnaire with references from the Cupe B.C. Consultant Firm Technological Change Questionnaire . The respondents were listed and selected according to the scope set. The research was performed in a sequential manner to obtain information as accurate as possible. Consequently, all data collected was being processed, analysed and evaluated.Results highlighted vendor performance based on four main criteria: organizational characteristics, workplace practices, employees’ involvement and employees training. Findings indicate that vendors are looking for a technology that can increase revenue and productivity. Investment made in machines and equipments are more significant than investment in people. Results also recognized managerial personnel as change champion. However, the overall results suggest that vendors understanding of this issue needs to be increased. It is hoped that this research will benefit the respondents in the form of a guidance, reference or even benchmark for the firms.